1997
DOI: 10.1093/ndt/12.12.2528
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated lipoprotein uptake by human glomerular cells: comparison with skin fibroblasts and HepG2 cells

Abstract: We conclude that glomerular epithelial and mesangial cells as well as skin fibroblasts and HepG2 exhibit VLDL receptors additionally to their LDL receptors, even though the regulation of the VLDL receptor in HepG2 cells seems to differ from the regulation in glomerular epithelial and mesangial cells. The high degradation-uptake-ratio in these renal cells suggests the presence of an effective clearance pathway which might serve as protection against lipoprotein accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Although no differences in renal tissue AmB concentra- tions were observed following Doc-AmB administration to cholesterol-fed rabbits, AmB's increased level of association with the TRL fraction may decrease AmB's ability to inflict renal damage at the cellular level. This may be because receptor-mediated uptake of apolipoprotein B-and E-rich lipoproteins (namely, LDL and TRL) by human glomerular epithelial cells (11,24) is downregulated in cholesterol-fed rabbits (11). Thus, most TRL-associated AmB, although delivered to the renal tissue, would not interact with kidney cells and would not cause damage.…”
Section: Discussionmentioning
confidence: 99%
“…Although no differences in renal tissue AmB concentra- tions were observed following Doc-AmB administration to cholesterol-fed rabbits, AmB's increased level of association with the TRL fraction may decrease AmB's ability to inflict renal damage at the cellular level. This may be because receptor-mediated uptake of apolipoprotein B-and E-rich lipoproteins (namely, LDL and TRL) by human glomerular epithelial cells (11,24) is downregulated in cholesterol-fed rabbits (11). Thus, most TRL-associated AmB, although delivered to the renal tissue, would not interact with kidney cells and would not cause damage.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, lipid-lowering therapy has been shown to improve glomerulosclerosis in the Zucker rat, a model of diabetes complicated with dyslipidemia [22]. Mesangial cells and glomerular epithelial cells (podocytes) have been shown to express receptors for TG-rich lipoproteins (TGRLs) [23][24][25][26]. TGRLs stimulate inflammatory pathways via the secretion of proinflammatory cytokines such as TNF-α, transforming growth factor (TGF)-β, and interleukin (IL)-6 [27], which results in the production of reactive oxygen species (ROS), leading to excessive ECM production.…”
Section: Impairment Of the Renal Function By Lipidsmentioning
confidence: 99%
“…In fact, glomerular cells like mesangial or epithelial cells have been shown in vitro to express lipoprotein receptors and to take up LDL comparably to fibroblasts and hepatocytes. 46 It is, however, completely unclear whether the kidney plays a significant role in LDL catabolism in vivo. Perfusion studies in rat kidneys indicated that virtually no intact LDL is cleared from the circulation by the kidney.…”
Section: Ikewaki Et Al Delayed Catabolism Of Idl and Ldl In Hemodialymentioning
confidence: 99%